PLAGIARISM ACROSS CULTURES: IS THERE A DIFFERENCE? - Joel Bloch (Universitas Katolik Indonesia Atma Jaya, 2007)
Trying to define plagiarism has been one of the most controversial issues in L2 writing classes. Much of the discussion has been about the relationship between how plagiarism is viewed in China and in the West, in part because there is a long, shared literacy tradition between them. This paper argues that while there are critical differences between how plagiarism is viewed, the relationship is often more complex than is sometimes thought. A study of this relationship can help us understand not only the nature of plagiarism but also concepts of imitation, originality, and authorship, which underlie how plagiarism is viewed. While the focus of this paper is on a comparison of Chinese- and English-language viewpoints, this perspective can help both researchers develop a framework for examining plagiarism across cultures and for teachers to develop a pedagogy for teaching about plagiarism that helps our students see its subtleties and contradictions involved in thinking about plagiarism in the same way they learn about any other aspect of literacy. Keywords: plagiarism, intercultural rhetoric, contrastive rhetoric, authorship, rhetoric